Hubungan Antara Berat Badan Bayi Lahir Dengan Status Gizi Bayi Usia 12 Bulan di Wilayah Kerja BPS Bd Titi Mulyani - Intan Khalifah (Jurnal Obstretika Scientia, 2021)
Nutritional status is a benchmark in assessing the growth and development of infants. In infants, nutritional status is influenced from the time of conception, pregnancy and birth. This period is known as the 1000 days of life, which is a sensitive period for child growth and development. If at this time the baby experiences nutritional problems, the consequences will be permanent. Factors history of birth weight also has an important role in influencing the nutritional status of infants. Babies born with low birth weight tend to have a lower immune system so they are more susceptible to infectious diseases. The purpose of this study was to determine the relationship between birth weight and the nutritional status of infants aged 12 months. The research method used is descriptive correlation with a cross sectional approach. The subjects in this study were infants aged 12-18 months. Sampling using total sampling. The independent variable in this study was the birth weight of the baby and the dependent variable was the infant's nutritional status. The results showed that there was a relationship between birth weight and the nutritional status of 12-month-old infants with a low level of closeness.